The postbiotic of hawthorn-probiotic ameliorates constipation by multi-pathway inhibition of PANoptosis in intestinal epithelial cells - Chen, Shiying; Lin, Jieling; Huang, Mengxia; Lin, Shi; Wei, Yu; Zhang, Cong; Huang, Yali (Frontiers in Immunology, 2025)
BackgroundConstipation is a common gastrointestinal disorder with significant public health implications, particularly among aging populations. Current treatment options often exhibit limited efficacy and may have potential side effects, underscoring the necessity for safer and more effective alternatives. Postbiotics, which are bioactive metabolites derived from probiotics, have emerged as promising therapeutic agents due to their stability, safety, and multifunctional properties. Postbiotic of hawthorn-probiotic has demonstrated potential in alleviating constipation; however, its mechanisms-particularly regarding the regulation of intestinal epithelial cell apoptosis and the gut microenvironment-remain to be fully elucidated.MethodsThis study employed murine models of loperamide-induced constipation and in vitro assays using NCM460 intestinal epithelial cells. Conditioned medium mimicking the gut microenvironment was prepared from colonic contents of different groups of mice. Cell viability and apoptosis levels were assessed using flow cytometry and fluorescence microscopy, while molecular pathways were analyzed through RT-qPCR and Western blot techniques. Network pharmacology was employed to integrate transcriptomic data for identifying core targets and pathways.ResultsPostbiotic of hawthorn-probiotic significantly downregulated apoptotic (CASP3, CASP9) and pyroptotic (NLRP3, GSDMD, CASP1) pathway components while restoring the balance of pro- and anti-apoptotic proteins (Bax/Bcl-2). Additionally, this postbiotic selectively modulated immune responses by reducing Th2/Th17-type cytokines (IL-2, IL-17A), without affecting Th1-type responses. Network analysis revealed that the action of hawthorn-probiotic postbiotics involves multiple targets including CASP8/CASP3-mediated cell death as well as STAT3/NF-κB signaling pathways.ConclusionsPostbiotic of hawthorn-probiotic demonstrates efficacy in alleviating constipation through the multi-pathway inhibition of apoptosis and pyroptosis, alongside the remodeling of the immune microenvironment. Its multi-target mechanism and favorable safety profile position it as a promising therapeutic candidate. These findings lay a solid foundation for the development of interventions based on hawthorn-probiotic postbiotics for constipation and related gastrointestinal disorders.